STUDI TINGKAT PENGETAHUAN DAN PERILAKU SWAMEDIKASI OBAT ANALGESIK PADA PASIEN DI APOTEK KOTA SAMARINDA - Susanti, Aprilia Diah; Dewi, Sinta Ratna (Jurnal Riset Kefarmasian Indonesia, 2022)
Self-medication is a behavior of the community to perform health treatment for themselves without having to consult with health workers. Analgesic is a non-steroidal anti-inflammatory drug (NSAID) group that is used to relieve pain, so it is often used by people to treat pain without losing awareness. This study aimed to describe the study of the level of knowledge and behavior of self-medication of analgesic drugs at the Samarinda City Pharmacy. This research is a type of quantitative research with the cross-sectional method. Sampling using non-probability sampling by purposive sampling. The sample used in this study was 147 respondents. The results showed that the majority of respondents on drug selection indicators (89.1%), drug class (83.65%), how to use (92.5%), and drug storage (75.96%) with behavioral levels on the selection indicator. drug (89.8%), drug class (87.1%), method of use (83.7%), and drug storage (77.5%). The patient's level of knowledge and the behavior of self-medication of analgesic drugs is included in the good category.